Pricing done right : the pricing framework proven successful by the worlds most profitable companies - Smith, Tim J. (Tim James) (Hoboken : Wiley, 2016)
"Practical guidance and a fresh approach for more accurate value-based pricing Pricing Done Right provides a cutting-edge framework for value-based pricing and clear guidance on ideation, implementation, and execution. More action plan than primer, this book introduces a holistic strategy for ensuring on-target pricing by shifting the conversation from 'What is value-based pricing?' to 'How can we ensure that our pricing reflects our goals?' You'll learn to identify the decisions that must be managed, how to manage them, and who should make them, as illustrated by real-world case studies. The key success factor is to build a pricing organization within your organization; this reveals the relationships between pricing decisions, how they affect each other, and what the ultimate effects might be. With this deep-level insight, you are better able to decide where your organization needs to go. Pricing needs to be done right, and pricing decisions have to be made--but are you sure that you're leaving these decisions to the right people? Few managers are confident that their prices accurately reflect the cost and value of their product, and this uncertainty leaves money on the table. This book provides a practical template for better pricing strategies, methods, roles, and decisions, with a concrete roadmap through execution. Identify the right questions for pricing analyses Improve your pricing strategy and decision making process Understand roles, accountability, and value-based pricing Restructure perspectives to help pricing reflect your organization's goals The critical link between pricing and corporate strategy must be reflected in the decision making process. Pricing Done Right provides the blueprint for more accurate pricing, with expert guidance throughout the change process"--
"Pricing Done Right provides a roadmap for the journey so they can get pricing done right as they implement the changes that will better position them for success"--
Appendix A: Economic Origins of Competitive AdvantageAppendix B: Getting Pricing Done with Jesse Finch Gnehm of GE Oil & Gas; The Value-Based Pricing Journey; Context of Subsea Systems within GE; Pricing Community Cultivation; Focal Contributions of the Pricing Experts; Pricing Framework; Pricing Analysis Techniques; Price Automation and Analytical Tools; External Resources; Appendix C: Getting Pricing Done with Robert Smith of Eastman Chemical Company; Pricing Organizational Design; Pricing Mission; Pricing Functional Architecture; About the Author; Index; EULA
Includes bibliographical references and index.
Machine generated contents note: Preface Acknowledgments Chapter 1: The Value-Based Pricing Framework for Getting Pricing Done Right Embedding the Culture of Value-based Pricing Overarching Pricing Decision Areas Analytical Routines Decision Teams Chapter 2: Value-Based Pricing The Purpose of Firms: Serve Customer Needs Profitably Value Engineering Value-Based Pricing Differential Benefits Differential Price Exchange Value to Customer Design Costs against Price to Profit References Chapter 3: Business Strategy Alignment Business Strategy Customers Competitors Company References Chapter 4: Pricing Strategy Price Positioning Price Segmentation Competitive Price Reaction Strategy Pricing Capability References Chapter 5: Price Management Market Pricing Price Variance Policy Price Execution Pricing Analysis Chapter 6: Defining the Pricing Decision Team Marketing Sales Finance Pricing References Chapter 7: Pricing Continuous Improvement and Analytics Continuous Improvement Process Offering Innovation and Pricing Decisions Price Variance Policy Continuous Improvement Market Pricing Continuous Improvement References Chapter 8: Organizational Design of the Pricing Specialist Function Pricing Community Distribution Pricing Reporting Structure Pricing Talent References Chapter 9: A Decision You Control References Appendix A: Economic Origins of Competitive Advantage Appendix B Getting Pricing Done with Jesse Finch Gnehm of GE Oil & Gas The Value-Based Pricing Journey Context of Subsea Systems within GE Pricing Community Cultivation Focal Contributions of the Pricing Experts Pricing Framework Pricing Analysis Techniques Price Automation and Analytical Tools External Resources Appendix C Getting Pricing Done with Robert Smith of Eastman Chemical Company Pricing Organizational Design Pricing Mission Pricing Functional Architecture About the Author Index.
Print version record.
John Wiley and Sons
Keywords: Pricing; Management; Price fixing; Prix -- Fixation; Gestion; management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Price fixing; Management; Pricing